Schwartz Value dan Perma Well-Being pada Dewasa Awal - Ni Luh Ayu Vivekananda; Evi Ema Vitoria Polii (Humanitas (Jurnal Psikologi), 2024)
PERMA Well-Being is a multidimensional concept that does not solely focus on Hedonic or Eudaimonic well-being but rather integrates both. In his model, Seligman identifies five dimensions of well-being: Positive Emotion, Engagement, Relationship, Meaning, and Accomplishment. Data analysis on the correlation between each Schwartz Value and the dimensions of PERMA: Multidimensional Framework of Well-Being, obtained from 495 respondents, indicates that the relationships between Schwartz Values and the dimensions of PERMA among emerging adults tend to be weak. Based on the PERMA dimensions, Engagement emerged as the highest dimension, while Positive Emotion and Meaning were the lowest. The depiction of Schwartz Values among emerging adults from diverse cultural backgrounds revealed Hedonism as the highest value and Power as the lowest. Future research is recommended to position Schwartz Values as moderators in the formation or enhancement of PERMA Well-Being. It is also suggested that subsequent studies not only focus on the five dimensions of PERMA Well-Being but also consider other factors influencing well-being, such as flow, gratitude, and happiness, to achieve a more comprehensive analysis of PERMA Well-Being.